Arterial blood gas analysis at different levels of altitude in healthy adult residents of Peru - Tinoco Solórzano, Amílcar (2017)
Objective: To know the values of arterial blood gases, SatO2, pO2/fiO2 and lactate in healthy high-altitude residents at two different levels of altitude. Materials and methods: Case report. Convenience sampling. Description of the values of arterial blood gases in the cities of Huánuco (1,818 masl) and Cerro de Pasco (4,380 masl). Results: In Huánuco and Cerro de Pasco we found the following values: pH: 7.42 (0.02) and 7.43 (0.01), pO2: 78.19 (4.76) and 54.18 (3.12), pO2/fiO2: 372.32 (22.66) and 258.13 (4.77), oxygen saturation: 96.24 (0.87) and 87.02 (2.31), lactate: 1.14 (0.49) and 1.47 (0.56), pCO2: 34.63 (3.62) and 27.69 (1.88), and HCO2: 22.56 (2.19) and 18.37 (1.33), respectively. Conclusions: The values of the arterial blood gas analysis in healthy high-altitude adult residents are different from the normal values in sea-level residents. The higher the altitude of residence, the more pronounced the changes.